Synthesis process of zero formaldehyde biomass adhesive

Through specific synthesis processes, zero formaldehyde biomass adhesives are prepared using biomass raw materials, solving the problems of insufficient performance and poor water resistance of existing biomass adhesives, and achieving high-performance, green and environmentally friendly adhesive products, suitable for a variety of application fields.

CN119752388APending Publication Date: 2025-04-04ANHUI WEICHUANG POLYMER MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411850299.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing biomass adhesives have problems such as insufficient performance, poor water resistance and high cost, which limits their wide application.

Method used

The biomass raw materials are used to prepare zero formaldehyde biomass adhesives through specific synthesis processes, including crushing and screening, high-temperature polycondensation reaction, polyisocyanate reaction, hydroxyepoxy resin grafting and diluent mixing.

Benefits of technology

The prepared zero-formaldehyde biomass adhesive has the characteristics of green and environmental protection, high performance, water resistance and strong weather resistance. It is suitable for a variety of application fields and has broad market prospects and promotion and application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752388A_ABST
    Figure CN119752388A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a zero-formaldehyde biomass adhesive synthesis process, comprising the following steps: crushing and screening biomass raw materials, castor oil and glycerol to achieve required particle size requirements; reacting the crushed and screened biomass raw materials, castor oil and glycerol, with an organic metal catalyst at high temperature under a nitrogen atmosphere to generate castor oil polyol; reacting the castor oil polyol with polyisocyanate in a reactor to synthesize a single-component polyurethane prepolymer; grafting a hydroxyl epoxy resin onto a polyurethane prepolymer molecular chain; mixing the grafting reaction product with a diluent in a mixer to obtain a zero-formaldehyde biomass adhesive; and refining the mixed adhesive to improve its uniformity and stability. The zero-formaldehyde biomass adhesive synthesis process prepares the zero-formaldehyde biomass adhesive through a specific synthesis process, so as to achieve the effects of being green and environmentally friendly, high-performance, water-resistant and strong weather resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a synthesis process of a zero-formaldehyde biomass adhesive. Background Art

[0002] Adhesive is a substance with excellent bonding properties. It connects objects by surface bonding through adhesion and cohesion. It can connect the same or two or more homogeneous or heterogeneous parts (or materials) together. It is an organic or inorganic, natural or synthetic substance with sufficient strength after curing. It is collectively called adhesive or bonding agent, adhesive, and is usually referred to as glue.

[0003] As the world's awareness of environmental protection increases, the release of harmful substances such as formaldehyde in traditional adhesives has attracted increasing attention. Formaldehyde is not only harmful to human health, but also pollutes the environment. Biomass adhesives have become an ideal choice to replace traditional adhesives due to their renewable, degradable and environmentally friendly raw materials.

[0004] However, the biomass adhesives currently on the market generally have problems such as insufficient performance, poor water resistance, and high cost, which limit their widespread application. This shows that we urgently need a zero-formaldehyde biomass adhesive synthesis process. Summary of the invention

[0005] In view of the above technical deficiencies, the purpose of the present invention is to provide a zero formaldehyde biomass adhesive synthesis process using biomass raw materials, prepared by a specific synthesis process, with the characteristics of green environmental protection, high performance water resistance, and strong weather resistance.

[0006] In order to solve the above technical problems, the present invention provides the following technical solution: a zero formaldehyde biomass adhesive synthesis process, comprising the following steps:

[0007] S1: crushing and screening the biomass raw materials, castor oil and glycerol to achieve the required particle size requirements;

[0008] S2: In a nitrogen atmosphere, the crushed and screened biomass raw materials castor oil and glycerol are reacted with an organic metal catalyst at high temperature to generate castor oil polyol;

[0009] S3: reacting castor oil polyol and polyisocyanate in a reactor to synthesize a one-component polyurethane prepolymer;

[0010] S4: Grafting hydroxy epoxy resin onto the molecular chain of polyurethane prepolymer to improve the performance of adhesive;

[0011] S5: mixing the product after the grafting reaction with a diluent in a mixer, adjusting the viscosity and fluidity of the adhesive, and preparing a zero-formaldehyde biomass adhesive;

[0012] S6: Refine the mixed adhesive to improve its uniformity and stability.

[0013] Preferably, in step S1, the biomass raw material is crushed and screened by a hammer mill and a screening device, and the size of the crushed particles is between 6 mm and 12 mm, and the maximum length does not exceed 30 mm.

[0014] Preferably, in step S2, at least two reaction kettles are provided, which are used for high-temperature polycondensation reaction and isocyanate reaction respectively, the high-temperature environment does not exceed 80°C, and the hydroxyl value of castor oil polyol is 300-480 mgOH / mol.

[0015] Preferably, in step S2, the organic metal catalyst comprises a plurality of organic metal catalysts selected from tin, titanium or zinc, and the amount of the organic metal catalyst used is 0.1% to 2% of the total mass of the reactants.

[0016] Preferably, in step S3, the polyisocyanate includes one or more selected from diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI) or isophorone diisocyanate (IPDI), and the R value of the single-component polyurethane prepolymer is controlled between 2.3 and 2.7.

[0017] Preferably, in step S4, the hydroxy epoxy resin comprises one or more hydroxy epoxy resins selected from bisphenol A type, bisphenol F type or aliphatic type, and the content of the epoxy resin in the final product is maintained between 5% and 9%.

[0018] Preferably, in step S5, the diluent comprises one or more diluents selected from acetone, butanone, ethyl acetate or toluene.

[0019] Preferably, in step S6, the zero formaldehyde biomass adhesive obtained by mixing is fed into a colloid mill for fine grinding, and the adhesive after the colloid milling treatment is fed into the feed port of a homogenizer, and the particles in the adhesive are further dispersed and evenly distributed in the liquid by the homogenizer, and finally stored in a storage tank, thereby improving the uniformity and stability of the adhesive.

[0020] Preferably, in step S3, the reaction temperature is controlled at 60-100°C, and the pressure is controlled at 0.1-0.5 MPa.

[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0022] First, the present invention uses a hammer mill to crush biomass raw materials, castor oil and propylene glycol to obtain particles with uniform particle size, and then uses a screening device to further ensure that the particle size is between 6 mm and 12 mm, and the maximum length does not exceed 30 mm, thereby ensuring the uniformity and efficiency of subsequent reactions. The raw materials derived from biomass are green, environmentally friendly and renewable. The products prepared from this resin have carbon fixation function, conform to the concept of sustainable development, have a wide range of material sources, a simple synthesis process, mild conditions, and low cost, and are suitable for large-scale promotion and application.

[0023] Second, the present invention feeds the raw materials castor oil and glycerol after crushing and screening into a reactor for high-temperature polycondensation reaction, and controls the temperature to not exceed 80°C to avoid overheating and decomposition of the raw materials. At the same time, an organic metal catalyst (such as tin, titanium or zinc compounds) is added, and its amount is accurately controlled to be 0.1% to 2% of the total mass of the reactants to accelerate the reaction and control the structure of the product, thereby reacting to generate castor oil polyol, whose hydroxyl value is in the range of 300-480mgOH / mol, which is a key raw material for the subsequent synthesis of polyurethane prepolymer, and then The obtained castor oil polyol is reacted with polyisocyanate (such as diphenylmethane diisocyanate MDI, toluene diisocyanate TDI or isophorone diisocyanate IPDI) in a second reactor, and the reaction temperature is controlled at 60-100°C and the pressure is controlled at 0.1-0.5MPa to ensure smooth reaction and control the molecular weight of the product. By adjusting the type and amount of polyisocyanate, the R value (isocyanate index) of the single-component polyurethane prepolymer is controlled between 2.3 and 2.7 to improve the crosslinking density and performance of the adhesive. Then, hydroxy epoxy resin (such as bisphenol A type, bisphenol F type or aliphatic type) is grafted onto the molecular chain segment of the prepolymer to form a higher density network structure with the polyurethane prepolymer, thereby improving the strength and durability of the adhesive. At the same time, the epoxy resin itself has good water resistance and weather resistance. After being grafted onto the polyurethane prepolymer, these properties will be transferred to the final adhesive product. By controlling the content of epoxy resin between 5-9%, the construction performance of the adhesive can be optimized, making it easier to apply and cure. Due to the high viscosity of hydroxy epoxy resin and polyurethane prepolymer, the adhesive can be easily coated and cured. The raw materials of the ester prepolymer all come from renewable resources, and no harmful substances such as formaldehyde are produced during the entire synthesis process. Therefore, the adhesive maintains its green and environmentally friendly characteristics. The adhesive after the grafting reaction is then mixed with a diluent (such as acetone, butanone, ethyl acetate or toluene) in a mixer to adjust the viscosity and fluidity of the adhesive for subsequent application, thereby obtaining a zero-formaldehyde biomass adhesive. The adhesive is not only green and environmentally friendly, but also has excellent water resistance and weather resistance. It is suitable for a variety of application fields and has broad market prospects and promotion and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1It is a flowchart of the overall process of the present invention;

[0025] Figure 2 This is a flowchart of step S1 of the present invention;

[0026] Figure 3 This is a flowchart of step S2 of the present invention;

[0027] Figure 4 This is a flowchart of step S3 of the present invention;

[0028] Figure 5 This is a flowchart of step S4 of the present invention;

[0029] Figure 6 This is a flowchart of step S5 of the present invention;

[0030] Figure 7 This is a flowchart of step S6 of the present invention. DETAILED DESCRIPTION

[0031] The specific implementation modes of the present invention will be further described in detail below with reference to the accompanying drawings. Specific implementation method 1

[0033] The following is a specific implementation method of the zero formaldehyde biomass adhesive synthesis process.

[0034] See also Figure 1-7 The synthesis process of zero formaldehyde biomass adhesive comprises the following steps:

[0035] S1: crushing and screening the biomass raw materials, castor oil and glycerol to achieve the required particle size requirements;

[0036] S2: In a nitrogen atmosphere, the crushed and screened biomass raw materials castor oil and glycerol are reacted with an organic metal catalyst at high temperature to generate castor oil polyol;

[0037] S3: reacting castor oil polyol and polyisocyanate in a reactor to synthesize a one-component polyurethane prepolymer;

[0038] S4: Grafting hydroxy epoxy resin onto the molecular chain of polyurethane prepolymer to improve the performance of adhesive;

[0039] S5: mixing the product after the grafting reaction with a diluent in a mixer, adjusting the viscosity and fluidity of the adhesive, and preparing a zero-formaldehyde biomass adhesive;

[0040] S6: Refine the mixed adhesive to improve its uniformity and stability.

[0041] Specifically, in step S1, the biomass raw material is crushed and screened by a hammer mill and a screening device, and the size of the crushed particles is between 6 mm and 12 mm, and the maximum length does not exceed 30 mm.

[0042] Specifically, in step S2, at least two reaction kettles are provided, which are used for high-temperature polycondensation reaction and isocyanate reaction respectively. The high-temperature environment does not exceed 80°C, and the hydroxyl value of castor oil polyol is 300-480 mgOH / mol.

[0043] Specifically, in step S2, the organic metal catalyst includes a plurality of organic metal catalysts selected from tin, titanium or zinc, and the amount of the organic metal catalyst used is 0.1% to 2% of the total mass of the reactants.

[0044] Specifically, in step S3, the polyisocyanate includes one or more selected from diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI) or isophorone diisocyanate (IPDI), and the R value of the single-component polyurethane prepolymer is controlled between 2.3 and 2.7.

[0045] Specifically, in step S4, the hydroxy epoxy resin includes one or more hydroxy epoxy resins selected from bisphenol A type, bisphenol F type or aliphatic type, and the content of the epoxy resin in the final product is maintained between 5% and 9%.

[0046] Specifically, in step S5, the diluent includes one or more diluents selected from acetone, butanone, ethyl acetate or toluene.

[0047] Specifically, in step S6, the zero-formaldehyde biomass adhesive obtained by mixing is fed into a colloid mill for fine grinding, and the adhesive after the colloid milling treatment is fed into the feed port of a homogenizer. The particles in the adhesive are further dispersed and evenly distributed in the liquid by the homogenizer, and finally stored in a storage tank, thereby improving the uniformity and stability of the adhesive.

[0048] Specifically, in step S3, the reaction temperature is controlled at 60-100° C., and the pressure is controlled at 0.1-0.5 MPa.

[0049] Through the above technical scheme, the biomass raw materials, castor oil and glycerol are crushed by a hammer mill to obtain particles with uniform particle size, and then the particle size is further ensured to be between 6 mm and 12 mm through screening equipment, and the maximum length does not exceed 30 mm, so as to ensure the uniformity and efficiency of subsequent reactions. The raw materials derived from biomass are green, environmentally friendly and renewable. The products prepared with this resin have carbon fixation function and conform to the concept of sustainable development. Then, the crushed and screened raw materials castor oil and glycerol are sent to the reactor for high-temperature polycondensation reaction, and the temperature is controlled at no more than 80°C to avoid overheating and decomposition of the raw materials. At the same time, an organic metal catalyst (such as tin, titanium or zinc compounds) is added, and its dosage is precisely controlled. The amount of castor oil polyol is 0.1% to 2% of the total mass of the reactants to accelerate the reaction and control the structure of the product, thereby generating castor oil polyol with a hydroxyl value in the range of 300-480 mgOH / mol, which is a key raw material for the subsequent synthesis of polyurethane prepolymers. The castor oil polyol obtained is then reacted with polyisocyanates (such as diphenylmethane diisocyanate MDI, toluene diisocyanate TDI or isophorone diisocyanate IPDI) in a second reactor. The reaction temperature is controlled at 60-100°C and the pressure is controlled at 0.1-0.5 MPa to ensure a smooth reaction and control the molecular weight of the product. By adjusting the type and amount of polyisocyanates, the R value (isocyanate index) of the single-component polyurethane prepolymer is controlled at 2. 3-2.7, improve the cross-linking density and performance of the adhesive, and then graft the hydroxy epoxy resin (such as bisphenol A, bisphenol F or aliphatic type) onto the prepolymer molecular chain segment to form a higher density network structure with the polyurethane prepolymer to improve the strength and durability of the adhesive. At the same time, the epoxy resin itself has good water resistance and weather resistance. After it is grafted onto the polyurethane prepolymer, these properties will be transferred to the final adhesive product. By controlling the content of epoxy resin between 5-9%, the construction performance of the adhesive can be optimized, making it easier to apply and cure. Since the raw materials of hydroxy epoxy resin and polyurethane prepolymer are all from renewable resources, and no harmful substances such as formaldehyde are produced during the entire synthesis process, the adhesive maintains The adhesive after the grafting reaction is mixed with a diluent (such as acetone, butanone, ethyl acetate or toluene) in a mixer to adjust the viscosity and fluidity of the adhesive for subsequent application, thereby obtaining a zero-formaldehyde biomass adhesive. The zero-formaldehyde biomass adhesive has the characteristics of being green and environmentally friendly, high-performance, water-resistant, and weather-resistant. It is suitable for home improvement, outdoor sports, automobiles and other fields, including but not limited to the manufacture of rose straw boards, molded pallets, wheat straw pallets, cork soles, automobile headlight assembly, front and rear windshield bonding and other products. In summary, the adhesive is not only green and environmentally friendly, but also has excellent water resistance and weather resistance. It is suitable for a variety of application fields and has broad market prospects and promotion and application value.

[0050] Although specific embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit thereof, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A zero-formaldehyde biomass adhesive synthesis process, characterized by: The following steps are involved: S1: crushing and screening the biomass raw materials, castor oil and glycerol to achieve the required particle size requirements; S2: In a nitrogen atmosphere, the crushed and screened biomass raw materials castor oil and glycerol are reacted with an organic metal catalyst at high temperature to generate castor oil polyol; S3: reacting castor oil polyol and polyisocyanate in a reactor to synthesize a one-component polyurethane prepolymer; S4: Grafting hydroxy epoxy resin onto the molecular chain of polyurethane prepolymer to improve the performance of adhesive; S5: mixing the product after the grafting reaction with a diluent in a mixer, adjusting the viscosity and fluidity of the adhesive, and preparing a zero-formaldehyde biomass adhesive; S6: Refine the mixed adhesive to improve its uniformity and stability.

2. The zero formaldehyde biomass adhesive synthesis process according to claim 1, characterized in that: In step S1, the biomass raw material is crushed and screened by a hammer mill and a screening device, and the size of the crushed particles is between 6 mm and 12 mm, and the maximum length does not exceed 30 mm.

3. The zero formaldehyde biomass adhesive synthesis process according to claim 1, characterized in that: In step S2, at least two reaction kettles are provided, which are used for high-temperature polycondensation reaction and isocyanate reaction respectively. The high-temperature environment does not exceed 80°C. The high-temperature polycondensation reaction time is 2-6 hours. The hydroxyl value of castor oil polyol is 300-480 mgOH / mol.

4. The zero formaldehyde biomass adhesive synthesis process according to claim 1, characterized in that: In step S2, the organic metal catalyst includes a plurality of organic metal catalysts selected from tin, titanium or zinc, and the amount of the organic metal catalyst used is 0.1% to 2% of the total mass of the reactants.

5. The zero formaldehyde biomass adhesive synthesis process according to claim 1, characterized in that: In step S3, the polyisocyanate includes one or more selected from diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI) or isophorone diisocyanate (IPDI), and the R value of the single-component polyurethane prepolymer is controlled between 2.3 and 2.

7.

6. The zero formaldehyde biomass adhesive synthesis process according to claim 1, characterized in that: In step S4, the hydroxy epoxy resin includes one or more hydroxy epoxy resins selected from bisphenol A type, bisphenol F type or aliphatic type, and the content of the epoxy resin in the final product is maintained between 5% and 9%.

7. The zero formaldehyde biomass adhesive synthesis process according to claim 1, characterized in that: In step S5, the diluent includes one or more diluents selected from acetone, butanone, ethyl acetate or toluene.

8. The zero formaldehyde biomass adhesive synthesis process according to claim 1, characterized in that: In step S6, the zero-formaldehyde biomass adhesive obtained by mixing is fed into a colloid mill for fine grinding, and the adhesive after the colloid milling treatment is fed into the feed port of a homogenizer. The particles in the adhesive are further dispersed and evenly distributed in the liquid by the homogenizer, and finally stored in a storage tank, thereby improving the uniformity and stability of the adhesive.

9. The zero formaldehyde biomass adhesive synthesis process according to claim 1, characterized in that: In step S3, the reaction temperature is controlled at 60-100°C and the pressure is controlled at 0.1-0.5 MPa.